2016
DOI: 10.1021/acs.macromol.5b02391
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Structure–Catalytic Activity Relationship in the Ring-Opening Polymerization of (Macro)lactones

Abstract: A kinetic analysis on the aluminum salen-catalyzed ring-opening polymerization (ROP) of (macro)­lactones is presented, which focuses on how chain transfer agents and the steric hindrance at the α-methylene groups of both the growing chain and the (macro)­lactones affect the polymerization rate. It is shown that for branched macrolactones the choice of initiator does not only influence the initiation rate but surprisingly also the apparent rate of polymerization. The increased polymerization rate, when an unbra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…It is quite notable that the catalysts were successful at both low monomer and catalyst concentrationsthere are few equivalent reports for other catalysts. 5j,11d One example, reported by Duchateau et al, 12 showed approximately equivalent conversion (57%) but requiring an hour using similar loadings ([PDL]/[Al] = 433, 0.23 mol%, [PDL] 0 = 1.3 M, at 373 K).…”
Section: Polymer Chemistry Papermentioning
confidence: 96%
“…It is quite notable that the catalysts were successful at both low monomer and catalyst concentrationsthere are few equivalent reports for other catalysts. 5j,11d One example, reported by Duchateau et al, 12 showed approximately equivalent conversion (57%) but requiring an hour using similar loadings ([PDL]/[Al] = 433, 0.23 mol%, [PDL] 0 = 1.3 M, at 373 K).…”
Section: Polymer Chemistry Papermentioning
confidence: 96%
“…The polyesters made of macrolactones (ML, large‐size lactones containing more than 11 atoms) have a hydrophobic character comparable to paraffins, and their potential for the design of biodegradable carriers suitable for drug dispensing applications has been extensively explored along the last decade . However ML‐based hybrid copolymers have been scarcely studied and the number of poly(macrolactone‐ co ‐α‐amino acid) copolymer systems known to date reduces to a couple of examples recently reported by us .…”
Section: Introductionmentioning
confidence: 99%
“…Bulky side chain plays an important role in steric hindrance effect (SHE) in chemical reactions . Furthermore, the performance of many optoelectronic devices, such as organic solar cells, OFET memories, was also deeply affected by SHE.…”
Section: Introductionmentioning
confidence: 99%